The Collective [videorecording (DVD)] (The Collective, 2004)
The Collective is a group of filmmakers, photographers, and mountain bikers. This group combines their experience, expertise, and creative energies to construct a film that highlights new, innovative images of free riding in mountains, the desert, and city environments.